Therapeutic Monoclonal Antibodies and Antibody Products, Their Optimization and Drug Design in Cancers - Kayser, Veysel (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The book broadly deals with therapeutic monoclonal antibodies (mAbs) and various relevant topics, including different antibody formats such as Antibody-Drug Conjugates (ADC), bispecifics, nanoparticle-based mAbs and HER2+ cancers, immune checkpoint inhibitors and other closely related topics. Each paper was written by leading active research groups in their fields both from academia and industry. The book should be of interest to those scientists and researchers who develop or use biologics, biotherapeutics, biosimilars and biobetters in cancer treatment.